Association of maternal genetic polymorphisms with fetal growth restriction syndrome in Russian pregnant women from Rostov region - Dema Alset; Elena Viktorovna Butenko; Inna Olegovna Pokudina; Tatiana Pavlovna Shkurat; Ekaterina Andreevna Zabanova; Natalia Borisovna Kuznetsova (Egyptian Journal of Medical Human Genetics, 2023)
Abstract Background Fetal growth restriction (FGR) is one of the main syndromes causing fetal morbidity and mortality. It was known to be associated with different factors including maternal, fetal, and environmental. However, the effect of genetic factors in FGR is not totally understood. Recently, researchers have focused on investigating genetic variants as possible markers of FGR. This especially concerns maternal genetic polymorphisms since they could serve as prenatal prognostic biomarkers. Accordingly, we aimed to study the association of several polymorphisms affecting vital processes of pregnancy with FGR in pregnant women. Targeted polymorphisms include methylenetetrahydrofolate reductase (MTHFR) 677C > T; methionine synthase reductase (MTRR) 66A > G; methionine synthase (MTR) 2756A > G; angiotensinogen (AGT) 704 T > C; and vascular endothelial growth factor A (VEGFA) 634C > G. In addition, this study examined SNP–SNP interactions, linkage disequilibrium (LD), and haplotypes association for these polymorphisms in the studied population. Results According to our data, MTRR 66(GG) carriers had increased FGR risk (OR = 3.18, 95% CI 1.31–7.72) while (AG) genotype was associated with lower FGR risk (OR = 0.37, 95% CI 0.17–0.84). AGT 704T > C also showed significant association with FGR with allele (T) as a risk factor. SNP–SNP interactions analysis revealed antagonistic relationship between these two polymorphisms and haplotypes association confirmed this finding. High LD possibility was shown between MTHFR 677C > T and MTR 2756A > G (D′ = 0.999) located on chromosome 1. Conclusion We suggest MTRR 66A > G and AGT 704T > C as associated with FGR susceptibility with antagonistic interaction. Result will help to expand our understanding of FGR as a multifactorial syndrome and improve prenatal prognosis using maternal genetic biomarkers, but further studies in different populations are needed to confirm findings.